Post-processor Program for ISO – 19902 Tubular Joints Design - Sambu Potty, Narayanan (2012)
This paper presents a postprocessor program for development for design of the tubular joints in ISO-19902 code. The program was developed using Mat Lab and NetBeans Java platform. Comparison of results showed that the unity check ratios obtained by using the post processor, were consistently lower than SACS’ joint can post processor. This paper also presents the design provision for the tubular joint of fixed offshore steel jacket platforms.